2017
DOI: 10.5897/jdae2017.0857
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of multidimensional poverty and its determinants in rural Nigeria

Abstract: Human beings live to get happiness, livelihood, peace, security, safety, dignity and respect among others. Deprivation of any of these could be frustrating. Thus, attempts were made to determine multidimensional poverty index (MPI) of rural households and its decomposition by geo-political zones in Nigeria using the Alkire-Foster MPI approach. The result showed that the headcount poverty ratio H was 78.1% when K = 30 as compared to 58.8% for K = 40 and 23.6% for K = 60. The adjusted headcount ratio also sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 11 publications
(16 reference statements)
5
16
1
Order By: Relevance
“…The multidimensional poverty index was 0.28, this implies that the rural households are deprived in 28% of the total deprivations they could experience overall. These findings differ from that of OPHI (2017) and Amao et al, (2017) that found out that the multidimensional poverty status of Ogun state and south-western Nigeria are 11.2% and 31.8% respectively.…”
Section: Deprivation Experienced By the Rural Householdscontrasting
confidence: 97%
“…The multidimensional poverty index was 0.28, this implies that the rural households are deprived in 28% of the total deprivations they could experience overall. These findings differ from that of OPHI (2017) and Amao et al, (2017) that found out that the multidimensional poverty status of Ogun state and south-western Nigeria are 11.2% and 31.8% respectively.…”
Section: Deprivation Experienced By the Rural Householdscontrasting
confidence: 97%
“…Therefore, households with more family members who are actively involved in family farm activities can manage their family farms easily, and the more economically active household members in a family, the less likely the family is to fall into poverty. This outcome supports the conclusions of Amao et al (2017), Heshmati & Yoon (2018, Michael et al (2019), andChen (2019) et al, who conducted a study on the determinants of multidimensional poverty and found that household size is negatively and significantly associated with multidimensional poverty. Spending per adult equivalent has a negative impact on the probability of households' multidimensional poverty status in the study area and is statistically significant at the 1% probability level.…”
Section: Ordered Logit Regression Results On the Determinants Of Mult...supporting
confidence: 86%
“…As a result, poverty will worsen in old age for household heads. The study's findings support those of Amao et al (2017), Michael et al (2019), and Chen (2019) et al, who conducted a study on the determinants of multidimensional poverty and found that the age of the household head is positively and significantly associated with multidimensional poverty.…”
Section: Ordered Logit Regression Results On the Determinants Of Mult...supporting
confidence: 85%
“…Alkire and Santos (2010), Alkire and Foster (2011), Alkire et al (2018), World Bank (2018), and Alkire et al (2014) represented education by school attendance and years of schooling; health by nutrition and child mortality; and living standards by cooking fuel, electricity, housing, improved water, improved sanitation, and asset ownership. Nonetheless, in other studies, particularly in those at the national level, including Woldehanna (2011), Mekonnen (2015), Tilman and Kebede (2013), and Joshua et al (2017), the dimensions and indicators differ across countries and scholars. This shows that the selection of dimensions and respective indicators for the estimation of poverty in a multidimensional approach depends on the socioeconomic characteristics and contexts.…”
Section: Data Source Methodology and Description Of Indicatorsmentioning
confidence: 94%
“…These studies were mainly based on three dimensions—education, health, and living standards—with 10 indicators for more than 104 countries. In contrast, there are studies undertaken at the national level, such as in South Africa by Rogan (2016), Brazil by Justino et al (2004), India by Alkire et al (2014), Nigeria by Joshua et al (2017), and in Uganda by Arinaitwe et al (2017). They consider country‐specific characteristics in their identification of dimensions and indicators.…”
Section: Literature Review and Gapsmentioning
confidence: 99%